The need for a more integrated approach between human and physical geography at university-level education in the Netherlands - Erik Meijles; Arie Stoffelen (Belgeo)
In this paper, we deconstruct how geography is organized as an academic study in the Netherlands. We consider how human and physical foci in geography are included in undergraduate and graduate curricula. As a country with a long academic history and renowned geography programmes, the minimal integration between human and physical geography that we identified is remarkable. We reflect on one high-profile societal debate to illustrate the limitations of the current way of conceptualizing geography as a degree programme: the case of human-induced earthquakes in the Dutch province of Groningen due to gas extraction. We argue that countries with academic geography education similar to the Netherlands stand to gain from embracing the integrative aspects to the field of geography. This is particularly the case when considering processes of global change that rapidly and, arguably, increasingly influence socio-spatial inequalities and livelihoods from global to local levels.